The Relationship between the Quality of Health Services and the Level of Patient Satisfaction at the Dr. Fauziah Regional General Hospital - Dwi Amalia Sari; Hernita Hernita; Khairiyatul Munawwarah (CV. AFDIFAL MAJU BERKAH, 2026)
The quality of health services is a crucial factor in determining patient satisfaction and the overall performance of health care institutions. High-quality services are expected to meet patient needs, improve trust, and enhance hospital utilization. This study aimed to examine the relationship between the quality of health services and the level of patient satisfaction at Dr. Fauziah Regional General Hospital. This research employed a quantitative approach with a cross-sectional design. A total of 44 outpatients were selected as respondents using accidental sampling. Data were collected using structured questionnaires and analyzed through univariate and bivariate analyses using the Chi-square test. The results showed that 79.6% of respondents perceived the quality of health services as good, and 79.6% of respondents reported being satisfied with the services received. Bivariate analysis indicated that there was no statistically significant relationship between the quality of health services and patient satisfaction (p = 0.200). In conclusion, although most patients perceived good service quality and reported satisfaction, the statistical analysis did not demonstrate a significant relationship between service quality and patient satisfaction at Dr. Fauziah Regional General Hospital.